On the social foundations for crimmigration: Latino threat and support for expanded police powers - Pickett, Justin T. (Journal of quantitative criminology, 2016)
Objectives Because of the merging of immigration control and criminal justice, or “crimmigration,” state and local police increasingly drive interior immigration enforcement through the routine policing of crime. At the same time, growing evidence indicates that immigration is an ethnicity-coded issue that allows for the veiled expression of broader anti-Latino sentiments. Yet little research has examined whether public perceptions of either immigrants or Latinos influence support for police policies and practices that, in the context of crimmigration, may significantly shape immigration enforcement and, more broadly, may contribute to the subordination of Latinos. The current study addresses this research question. Methods The study draws on data from a recent nationally representative telephone survey and employs multivariate regression methods to evaluate whether perceptions of Latino economic and political threat are associated with support for granting police greater latitude in stopping, searching, and using force against suspects. Results This study provides the first evidence that, at least among Whites, perceived Latino threat is positively associated with support for expanding police investigative powers, especially the power to stop suspects based only on the way they look. Conclusions The results suggest that by increasing public support for aggressive policing, or, at minimum, by reducing opposition to discriminatory social controls such as police profiling, Latino threat perceptions may increase the political attractiveness and viability of crimmigration as a “solution” to the “Latino problem.”